Analisis Problematika Penerapan Etika Profesi Advokat sebagai Upaya Pengawasan Profesionalisme Advokat dalam Hal Penegakan Hukum - Della Rolansa; Baidhowi (CV Rewang Rencang, 2022)
Advocate is an honorable law enforcement profession (Officium Nobile) because it devotes itself to the community through the legal services provided. However, the practice is often found that advocates do not carry out their professional obligations and even violate the law and are not professional. The purpose of this paper is to find out professional ethics as an effort to supervise the professionalism of law enforcement and how problems in its implementation. The writing method used is empirical juridical, the writing of which is carried out by researching reality in the field through the collection of facts with interviews. The results obtained ideally professional ethics act as a guideline for moral and behavioral control that imposes sanctions focused psychologically and institutionally in order to form a strong moral integrity for advocates to work professionally and avoid conflicts of interest. Still, in its implementation, there are many obstacles such as the absence of internalization of professional ethical values in each individual advocate resulting in unfair law enforcement and unlawful actions of advocates.